Reevaluating the Sperm Nuclear Chromatin Decondensation Test by Sodium Thioglycolate of Stallions Spermatozoa - Hartley, Ricardo; Aros, Pablo; Bustos-Obregón, Eduardo; Romero, Fernando; Alvarenga, Marco [UNESP]; Ramírez-Reveco, Alfredo (Elsevier, 2016)
The nucleus of mammalian spermatozoa is mainly composed of chromatin associated with protamines: highly basic proteins (around 7 kDa). These highly basic proteins, due to their cysteine content, can participate in the generation of disulfide bond. These characteristics permit typical condensed nuclear structure in mature spermatozoa, where the DNA becomes organized in compacted units, similar to nucleosomes, but with 60 kb of DNA. This shape is ultimately assumed in the epididymal maturation, and the level of compaction is closely related to epididymal function. In the present work, we present a modified method to evaluate sperm decompaction using sodium thioglycolate (ST). Stallion sperm were exposed to different ST concentrations and were embedded in agarose as a supportive medium. With the use of agarose, it was easier to identify patterns of decompaction with ST, and, thus, the use of a permeabilizing solution was not necessary. This was due to the utilization of ST to evaluate chromatin compaction of stallion sperm physically permeabilized and embedded in agarose matrix.
Keywords: Chromatin compaction; Sodium thioglycolate; Sperm nucleus; Stallion